In Vitro Effect of Mouthrinses on the Microhardness of Three Different Nanohybrid Composite Resins - Jhonn Luis Bernaldo-Faustino; Julissa Amparo Dulanto-Vargas; Kilder Maynor Carranza-Samanez (Hindawi Limited, 2023)
Introduction. Daily use of different mouthrinses at home or in the dental office can alter the properties of resin hardness. The present study aimed to compare Vickers microhardness (VHN) in vitro of nanohybrid composite resins (NCRs) immersed in mouthrinses. Materials and Methods. In total, 120 discs (10 ⨯ 2 mm) were prepared from three NCR shade A2 (n = 40/group) with FiltekTM Z350 XT (Z350XT), Tetric EvoCeram (TEC), and Polofil NHT (PNHT). The specimens were incubated in artificial saliva (37°C ⨯ 24 hr). Specimens were distributed into four mouthrinses (n = 10/group) of artificial saliva (control), chlorhexidine (CHX 0.12%, pH 5.6), cetylpyridine chloride (CPC 0.075%, pH 5.84), and CHX 0.12% + CPC 0.05% (pH 6.2) (2 times/day, 2' ⨯ 12 hr). The VHN (300 gf/10") was measured after 24 hr, 14, and 21 days. Data were analyzed by three-way analysis of variance, followed by post hoc Tukey analysis at 0.05 level of significance. Results. The results revealed a global effect of the interaction of the mouthrinses ⨯ time between NRC evaluated (P=0.001). Baseline VHN in PNHT and Z350XT was higher than TEC. Within each group of NCR, VHN of CHX + CPC > other mouthrinses (PNHT/14 days; Z350XT/21 days), and >CPC (Z350XT/14 days). In mouthrinses-intragroups, VHN of PNHT and Z350XT decreased at 14 days (CHX, CPC) and was maintained over time in NCR (CHX + CPC). VHN-TEC was similar among groups. Conclusion. Microhardness showed differences due to the interaction of the type of NCR, the composition of the mouthrinses, and time. VHN decreased after 14 days and was more affected in composite resins with lower filler content and in mouthrinses with a lower pH.